Implementation of Simdiklat and User Satisfaction Among Employees of BBPPMPV BOE Malang - Zahrul Andriansyah; Syaifuddin Fahmi; Handik Purwantoro (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted at BBPPMPV BOE Malang, a government institution that provides education and training to vocational high school teachers in the field of technology in the eastern region of Indonesia. Since 1986, they have developed the simdiklat application to manage administrative data using the Single Entry Multi Output concept. The objective is to enhance effectiveness, efficiency, service quality, and user satisfaction. The research population consisted of 40 simdiklat users, and the entire population was taken as the sample. The analysis was conducted using SPSS (Statistical Package for the Social Sciences). The findings indicate that the implementation of simdiklat plays a significant role in improving user satisfaction among employees of BBPPMPV BOE Malang.